Оцінка рівня забезпечення якості послуг автосервісу - Кузьмін, В. С. (НТУ "ХПІ", 2013)
На основі аналізу раніше виконаних робіт і теоретичних досліджень розроблено модель і систему забезпечення якості послуг підприємства автосервісу. Розглянуто та визначено вимоги та умови формування системи оцінки рівня забезпечення, представлено загальну методику та порядок оцінки. Наведено рекомендації по визначенню коефіцієнта якості забезпечення виробничого процесу і послуги

On the basis of the analysis before the executed works and theoretical researches the model and system of maintenance of quality of services of the enterprise of car-care centre is developed. Requirements and conditions of formation of system of an estimation of level of maintenance are considered and defined, the general technique and an estimation order is presented. Recommendations about definition of factor of quality of maintenance of production and service are resulted
Keywords: оцінювані параметри; показники якості; методика оцінки; керівник; споживачі; нормативи; quality of the services; estimated parametres; quality indicators; estimation technique